2011
DOI: 10.1128/jcm.01885-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fluoroquinolone-Resistant Organisms from Rectal Swabs by Use of Selective Media Prior to a Transrectal Prostate Biopsy

Abstract: Sepsis caused by fluoroquinolone-resistant Escherichia coli is a risk for patients undergoing an ultrasoundguided, transrectal prostate biopsy. A method incorporating selective broth and media was evaluated using rectal swabs obtained from 136 patients prior to a biopsy procedure. Fluoroquinolone-resistant organisms were isolated from 22% of the patients included in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
5
19
0
Order By: Relevance
“…There is no established evidence to indicate the optimal laboratory screening technique and appropriate duration between prebiopsy screening and prostate biopsy. 30,32 There is emerging evidence demonstrating the benefit of increasing the conventional ciprofloxacin regimen with aminoglycosides. 33,34 The Canadian guidelines recommend the addition of intravenous aminoglycosides to FQ in centeres with a high post-biopsy UTI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…There is no established evidence to indicate the optimal laboratory screening technique and appropriate duration between prebiopsy screening and prostate biopsy. 30,32 There is emerging evidence demonstrating the benefit of increasing the conventional ciprofloxacin regimen with aminoglycosides. 33,34 The Canadian guidelines recommend the addition of intravenous aminoglycosides to FQ in centeres with a high post-biopsy UTI incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin resistance may be identified through a review of medical notes and previous urine cultures. Liss et al [9] found that 22% of their patients had fluoroquinolone resistant organisms on rectal swab prior to biopsy. In patients where there is suspicion of resistance a broad spectrum antibiotic should be added [10].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown that up to 22 % of men who receive a prostate biopsy have positive cultures of fl uoroquinolone resistant bacteria from their rectums, and that these same men were also likely to have taken a fl uoroquinolone within the previous 6 months [ 51 ]. Kamdar et al found that hospital employees may become asymptomatically colonized with high-risk multidrug resistant bacteria from their work environments and subsequently contribute to the colonization of their family members.…”
Section: Infection Epidemiologymentioning
confidence: 98%